Justin Presents the Divinity of Christ before Jews and Pagans (Teología, 2018)
The autor gives us a brief account of Saint Justinô€€€s vision of the Trinity, which is fruit of a long research. Firstly, it summarizes the line of thought of the Dialog, where Justin adscribes to the Logos the theophanies of the Old Testament. This God is distinct in number from the Father Creator of the Universe, but is placed below Him. In the Apologies, instead, Justin confronts both paganism and Platonism: he places the Logos in the second place, and the Spirit in the third. The Son, only-begotten, is begotten from the Father before all creatures, without dividing Him, like a fire lights another fire. The Father makes everything through Him. Justin makes only a few allusions to the activity proper to the prophetic Spirit. These two paths meet toghether in a certain inferiority of the Son in relation to the Father, which is tipical of various Pre-Nicean Fathers. The evil demons have persecuted all those who, like Socrates, have lived according to the Logos. Plato copied Moses without having undestood him completely. The cross of the Son is cosmic. Jesus is the crucified Master.
Keywords: Justin; Logos; Subordinatianism; Christian Socrates